2010
DOI: 10.1111/j.1582-4934.2008.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Tau dephosphorylation and microfilaments disruption are upstream events of the anti‐proliferative effects of DADS in SH‐SY5Y cells

Abstract: Garlic organosulphur compounds have been successfully used as redox anti-proliferative agents. In this work, we dissect the effects of diallyl disulphide (DADS) focusing on the events upstream of cell cycle arrest and apoptosis induced in neuroblastoma SH-SY5Y cells. We demonstrate that DADS is able to cause early morphological changes, cytoskeleton oxidation, microfilaments reduction and depolymerization of microtubules. These events are attenuated in cells stably overexpressing the antioxidant enzyme SOD1, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
(108 reference statements)
0
22
0
Order By: Relevance
“…We previously showed that the organosulfur compound diallyl disulfide (DADS) inhibits neuroblastoma cells growth and finally induces mitochondrial-dependent apoptosis [21]. In particular, we demonstrated that the anti-proliferative action of DADS relays on its pro-oxidant function acting at two different levels: i) ROS-mediated induction of apoptotic phosphorylative cascade managed by JNK/cJun; ii) ROS-mediated disruption of cytoskeletal lattice functioning as a widespread anti-cytoskeletal agent against both actin and tubulin [21,22]. However, DADS is not able to induce very high rate of apoptosis in neuroblastoma cells if compared to other cell lines, indicating the occurrence of adaptive responses [23].…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that the organosulfur compound diallyl disulfide (DADS) inhibits neuroblastoma cells growth and finally induces mitochondrial-dependent apoptosis [21]. In particular, we demonstrated that the anti-proliferative action of DADS relays on its pro-oxidant function acting at two different levels: i) ROS-mediated induction of apoptotic phosphorylative cascade managed by JNK/cJun; ii) ROS-mediated disruption of cytoskeletal lattice functioning as a widespread anti-cytoskeletal agent against both actin and tubulin [21,22]. However, DADS is not able to induce very high rate of apoptosis in neuroblastoma cells if compared to other cell lines, indicating the occurrence of adaptive responses [23].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence, conversely, indicates that OSCs induce strong alterations of MT re-arrangement (see figure 3 and section 3.2). This property is common to different natural occurring OSCs manifesting apoptogenic properties on the different cancer cell models (Aquilano et al, 2010;Hosono et al, 2005;Li et al, 2002a;Prager-Khoutorsky et al, 2007;Xiao et al, 2005;Xiao et al, 2003).…”
Section: Alterations Induced By Oscs On the Mt Network As A Causativementioning
confidence: 97%
“…These studies suggested that polysulfide/ajoene-induced apoptotic cell death is caused by ROS accumulation and peroxide production (Aquilano et al, 2010;Charlier et al, 2010;Dirsch et al, 1998;Wang, H.C. et al, 2010a). DADS, DATS and DATTS and to a lesser extent the corresponding propylsulfides have been identified as hemolytic agents, as they induce oxidative damage in erythrocytes by the formation of H 2 O 2 in the presence of GSH and haemoglobin (Munday et al, 2003).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…DADS treatment alone was reported to be effective in inhibiting cancer cell growth, inducing apoptosis and causing partial G2/M cell cycle arrest in cancers of colon, pancreas, prostate, lung, brain, and stomach (Aquilano et al 2010;Bo et al 2014;Bottone et al 2002;Gunadharini et al 2006;Song et al 2009;Wu et al 2005). In particular, the anticancer proliferation effects were reported to be associated with an increase in reactive oxygen species (ROS) production.…”
Section: Classification Of H 2 S Donorsmentioning
confidence: 98%
“…In particular, the anticancer proliferation effects were reported to be associated with an increase in reactive oxygen species (ROS) production. For instance, DADS was shown to induce cytoskeleton oxidation and microtubule depolymerization, thence morphological changes in neuroblastoma SH-SY5Y cells (Aquilano et al 2010). However, these effects were reversed by administration of exogenous precursors of cellular antioxidants, N-acetylcysteine (NAC) or glutathione ester.…”
Section: Classification Of H 2 S Donorsmentioning
confidence: 98%